Polyvinyl alcohol-based composite film as well as preparation method and application thereof
By adding fluorine graphene nanosimal tablets and carboxymethyl shell polycosan to polyvinitol, a high -efficiency thermal conductivity network is formed, the problem of multi -performance decline in polyethylene glycolic material in the improvement of thermal conductivity, and the polyvinyl alcohol group The multi -performance improvement and application of composite membranes are widely used.
Patent Information
- Application Number
- CN202411640502.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-18
Smart Images

Figure CN119371764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyvinyl alcohol-based composite film with high insulation and high thermal conductivity, belonging to the technical field of functional nano materials. Background Art
[0002] As the core of modern power electronic equipment, power electronic components have been used in various fields as never before. Due to the requirements of the use environment, it is usually necessary to coat or prepare one or more layers of protective film on the surface of power electronic components to enable the power electronic components to resist adverse effects such as static electricity and oxidative corrosion, and at the same time, to quickly and effectively conduct away the large amount of heat generated by the power electronic components during operation. This requires that the material used as the protective film has good mechanical, chemical and thermal stability, good insulation and thermal conductivity, and at the same time, the manufacturing process is simple and the cost is low.
[0003] Polyvinyl alcohol (PVA) is a non-toxic, odorless, biodegradable insulating linear polymer. In recent years, it has been widely used in adhesives, hydrogels, optoelectronic matrices, pharmaceuticals, and biology. Polyvinyl alcohol can also be used as a good matrix for thermal interface materials due to its good mechanical, chemical, and thermal stability, but its thermal conductivity is very low, which limits its further application in thermal management.
[0004] At present, there are two ways to construct a continuous thermal conductive network in polyvinyl alcohol to improve its thermal conductivity: (1) increase the coupling strength between chains through hydrogen bond crosslinking or chemical crosslinking. Although heterogeneous molecules can connect adjacent main chains through coupling to form a thermal conductive network, due to the low intrinsic thermal conductivity of polyvinyl alcohol, this connection method has limited or negligible contribution to thermal conductivity; (2) add high thermal conductivity fillers, such as graphene oxide, carbon nanotubes, and boron nitride. However, these fillers will reduce the crystallinity of polyvinyl alcohol, and thus the improvement of thermal conductivity is limited.
[0005] As a material with good thermal stability, chemical stability and electrical properties, fluorinated graphene can be considered as a high thermal conductivity filler added to polyvinyl alcohol. However, existing studies have shown that excessive addition of fluorinated graphene will destroy the mechanical properties and crystal structure of polyvinyl alcohol, reduce its flexibility and tensile strength, and is not conducive to further application. When a small amount of fluorinated graphene is added to polyvinyl alcohol, polyvinyl alcohol will connect the fluorinated graphene through hydrogen bonds and orient it and crystallize at its edges, but when it reaches the dispersion threshold in polyvinyl alcohol, it cannot form a thermal conductive network, which limits the substantial improvement of thermal conductivity. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a polyvinyl alcohol-based composite film and a preparation method thereof, wherein a high-efficiency thermal conductive network consisting of carboxymethyl chitosan-crystalline region-fluorinated graphene is formed inside the composite film, and the composite film has excellent electrical insulation properties, mechanical properties and thermal properties.
[0007] The present invention specifically adopts the following technical solutions to solve the above technical problems:
[0008] A polyvinyl alcohol-based composite film is composed of polyvinyl alcohol, fluorinated graphene nanosheets (FGN) and carboxymethyl chitosan (CMC) in a mass ratio of 100:1.1 to 8.2:8.7. The polyvinyl alcohol is connected to the fluorinated graphene nanosheets through hydrogen bonds and is directionally arranged and crystallized at the edges thereof. The carboxymethyl chitosan couples adjacent polyvinyl alcohol crystal regions through hydrogen bonds, thereby forming a highly efficient thermal conductive network consisting of carboxymethyl chitosan-crystal region-fluorinated graphene.
[0009] Preferably, the mass ratio of polyvinyl alcohol, fluorinated graphene nanosheets and carboxymethyl chitosan is 100:1.1 to 3.4:8.7.
[0010] More preferably, the mass proportion of the fluorinated graphene nanosheets is 3%.
[0011] The method for preparing a polyvinyl alcohol-based composite film as described in any of the above technical schemes is to mix a polyvinyl alcohol aqueous solution with a concentration of 20 to 50 mg / mL and a fluorinated graphene nanosheet aqueous dispersion of 0.5 to 1 mg / mL according to the mass ratio, and then add 20 to 30 mg / mL of carboxymethyl chitosan aqueous dispersion and mix evenly. After vacuum drying at a temperature of 60°C to 80°C to form a film, it is peeled off from the carrier.
[0012] Preferably, the preparation method of the fluorinated graphene nanosheets is as follows: dispersing the fluorinated graphene in a solvent, and subjecting the solvent to ultrasonic and centrifugal treatment to obtain exfoliated fluorinated graphene nanosheets.
[0013] Further preferably, the ultrasonic treatment is performed using a water bath sonicator, the power of the water bath sonicator is 30 to 100 W, and the ultrasonic time is 18 to 32 hours; the rotation speed of the centrifugal treatment is 3000 to 6000 rpm, and the treatment time is 15 to 30 minutes.
[0014] More preferably, the solvent is one or more of isopropanol, N-methylpyrrolidone, N,N-dimethylformamide and dichloromethane.
[0015] Preferably, the fluorinated graphene nanosheet aqueous dispersion, the polyvinyl alcohol aqueous solution and the carboxymethyl chitosan aqueous dispersion are uniformly mixed by ultrasound and stirring.
[0016] The polyvinyl alcohol-based composite film as described in any of the above technical solutions is used as a protective film on the surface of power electronic components.
[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0018] (1) The composite membrane proposed in the present invention uses polyvinyl alcohol as a polymer matrix and is modified with low-filling content fluorinated graphene nanosheets and carboxymethyl chitosan. Polyvinyl alcohol connects to fluorinated graphene through hydrogen bonds and is oriented and crystallized at its edges, while carboxymethyl chitosan couples adjacent crystal regions through hydrogen bonds to form a unique high-efficiency thermal conductive network consisting of carboxymethyl chitosan-crystal region-fluorinated graphene.
[0019] (2) The composite film of the present invention has excellent electrical insulation properties, mechanical properties and thermal properties. When the contents of fluorinated graphene nanosheets and carboxymethyl chitosan are 3wt.% and 7.76wt.%, respectively, the in-plane thermal conductivity of the polyvinyl alcohol-based composite film is 12.22W / (m·K), which is 5.2 times that of polyvinyl alcohol; the out-of-plane thermal conductivity is 0.41W / (m·K), which is 5.1 times that of polyvinyl alcohol, and the thermal decomposition temperature is increased by 57°C. The composite film can be widely used in applications with high requirements for thermal conductivity and insulation, such as on the surface of power electronic components. While ensuring electrical insulation, the upper limit of the operating temperature of the components can be greatly increased through good heat dissipation.
[0020] (3) The present invention adopts a solution casting method to connect fluorinated graphene nanosheets and carboxymethyl chitosan in polyvinyl alcohol and form a continuous thermal conductive network. The preparation process is simple, the preparation cost is low, and it is suitable for large-scale production. After the film is prepared, it has a tensile strength close to that of polyvinyl alcohol and excellent insulation properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The scanning electron microscope images of the film of comparative example 1 and the films of embodiments 2 and 3; wherein (a), (b), and (c) correspond to the surfaces of the three films respectively, and (d), (e), and (f) correspond to the brittle fracture surfaces of the three films respectively;
[0022] Figure 2 DSC curves of the films of Comparative Examples 1 to 3 and Examples 1 to 4;
[0023] Figure 3 The stress-strain curves and volume resistivity diagrams of the films of Comparative Examples 1 to 3 and Examples 1 to 4, wherein (a) is the stress-strain curve and (b) is the volume resistivity;
[0024] Figure 4 The thermal conductivity bar graphs of the films of Comparative Examples 1 to 3 and Examples 1 to 4, wherein (a) is the in-plane thermal conductivity and (b) is the out-of-plane thermal conductivity;
[0025] Figure 5 It is a red thermal imaging comparison diagram of the films of comparative examples 1 to 3 and example 2; wherein (a) is an infrared thermal imaging diagram of an LED bulb with the films of comparative examples 1 to 3 and example 2 as substrates, respectively, and (b) is an infrared thermal imaging diagram of the films of comparative examples 1 to 3 and the example film in the vertical direction. DETAILED DESCRIPTION
[0026] The inventors found that polyvinyl alcohol is used as a polymer matrix and is modified with fluorinated graphene nanosheets and carboxymethyl chitosan with a low filling content. Polyvinyl alcohol is connected to fluorinated graphene through hydrogen bonds, and is directionally arranged and crystallized at the edges of the fluorinated graphene nanosheets to form a large number of crystal regions. Carboxymethyl chitosan couples adjacent crystal regions through hydrogen bonds, thereby forming a unique and efficient thermal conductive network consisting of carboxymethyl chitosan-crystal region-fluorinated graphene. This thermal conductive network enables the composite film to have extremely excellent electrical insulation properties, mechanical properties and thermal properties.
[0027] Based on the above findings, the inventors proposed the following technical solutions:
[0028] A polyvinyl alcohol-based composite film is composed of polyvinyl alcohol, fluorinated graphene nanosheets and carboxymethyl chitosan in a mass ratio of 100:1.1 to 8.2:8.7. The polyvinyl alcohol is connected to the fluorinated graphene nanosheets through hydrogen bonds and is directionally arranged and crystallized at their edges. The carboxymethyl chitosan couples adjacent polyvinyl alcohol crystal regions through hydrogen bonds, thereby forming a highly efficient thermal conductive network consisting of carboxymethyl chitosan-crystal region-fluorinated graphene.
[0029] Preferably, the mass ratio of polyvinyl alcohol, fluorinated graphene nanosheets and carboxymethyl chitosan is 100:1.1 to 3.4:8.7.
[0031] More preferably, the mass proportion of the fluorinated graphene nanosheets is 3%.
[0032] The method for preparing a polyvinyl alcohol-based composite film as described in any of the above technical schemes is to mix a polyvinyl alcohol aqueous solution with a concentration of 20 to 50 mg / mL and a fluorinated graphene nanosheet aqueous dispersion of 0.5 to 1 mg / mL according to the mass ratio, and then add 20 to 30 mg / mL of carboxymethyl chitosan aqueous dispersion and mix evenly. After vacuum drying at a temperature of 60°C to 80°C to form a film, it is peeled off from the carrier.
[0033] Preferably, the preparation method of the fluorinated graphene nanosheets is as follows: dispersing the fluorinated graphene in a solvent, and subjecting the solvent to ultrasonic and centrifugal treatment to obtain exfoliated fluorinated graphene nanosheets.
[0034] Further preferably, the ultrasonic treatment is performed using a water bath sonicator, the power of the water bath sonicator is 30 to 100 W, and the ultrasonic time is 18 to 32 hours; the rotation speed of the centrifugal treatment is 3000 to 6000 rpm, and the treatment time is 15 to 30 minutes.
[0035] Preferably, the solvent is one or more of isopropanol, N-methylpyrrolidone, N,N-dimethylformamide and dichloromethane.
[0036] Preferably, the fluorinated graphene nanosheet aqueous dispersion, the polyvinyl alcohol aqueous solution and the carboxymethyl chitosan aqueous dispersion are uniformly mixed by ultrasound and stirring.
[0037] The polyvinyl alcohol-based composite film as described in any of the above technical solutions is used as a protective film on the surface of power electronic components.
[0038] In order to facilitate public understanding, the technical solution of the present invention is described in detail below through several specific embodiments and in combination with the accompanying drawings. The polyvinyl alcohol, fluorinated graphene and carboxymethyl chitosan used in each embodiment are commercial materials purchased from the market, wherein the molecular weight of polyvinyl alcohol is 1.45×10 5 ; The size of fluorinated graphene is 5-10 μm, and the fluorine-carbon ratio is 1.1:1; The degree of substitution of carboxymethyl chitosan is ≥80%:
[0039] Example 1
[0040] (1) A suspension of fluorinated graphene and N-methylpyrrolidone was refluxed at 80°C for 2 h, ultrasonicated (40 W) for 24 h, and then centrifuged at 3000 and 6000 rpm for 30 min, respectively; the precipitate at 6000 rpm was washed with deionized water, filtered and freeze-dried to obtain fluorinated graphene nanosheets; and finally, the precipitate was redispersed in water under ultrasonication to obtain a 0.50 mg / mL aqueous dispersion of fluorinated graphene nanosheets.
[0041] (2) Add 2 g of polyvinyl alcohol particles into a beaker containing 100 mL of deionized water, stir at 80° C. until completely dissolved, and add deionized water to the 100 mL mark to obtain a 20 mg / mL polyvinyl alcohol aqueous solution.
[0042] (3) Add 2 g of carboxymethyl chitosan powder into a beaker containing 100 mL of deionized water and stir until dissolved to obtain a 20 mg / mL carboxymethyl chitosan aqueous solution.
[0043] (4) First, 6.83 mL of polyvinyl alcohol aqueous solution was slowly dripped into 3.00 mL of fluorinated graphene nanosheet dispersion under stirring; the mixed solution was ultrasonicated for 10 min and stirred for 30 min; then, 0.59 mL of carboxymethyl chitosan aqueous dispersion was slowly dripped into it under stirring, and stirring was continued for 30 min; finally, the prepared mixed solution was poured into a quartz watch glass and dried in a conventional oven at a temperature of 60°C to obtain a uniform light yellow transparent polyvinyl alcohol-based composite film, wherein the mass ratio of polyvinyl alcohol, fluorinated graphene nanosheets, and carboxymethyl chitosan was 100:1.1:8.7. The polyvinyl alcohol-based composite film prepared in this example is hereinafter referred to as PCF-1.
[0044] Example 2
[0045] (1) A suspension of fluorinated graphene and N-methylpyrrolidone was refluxed at 80°C for 2 h, ultrasonicated (40 W) for 24 h, and then centrifuged at 3000 and 6000 rpm for 30 min, respectively; the precipitate at 6000 rpm was washed with deionized water, filtered and freeze-dried to obtain fluorinated graphene nanosheets; and finally, the precipitate was redispersed in water under ultrasonication to obtain a 0.5 mg / mL aqueous dispersion of fluorinated graphene nanosheets.
[0046] (2) Add 3 g of polyvinyl alcohol particles into a beaker containing 100 mL of deionized water, stir at 80° C. until completely dissolved, and add deionized water to the 100 mL mark to obtain a 30 mg / mL polyvinyl alcohol aqueous solution.
[0047] (3) Add 2 g of carboxymethyl chitosan powder into a beaker containing 100 mL of deionized water and stir until dissolved to obtain a 20 mg / mL carboxymethyl chitosan aqueous solution.
[0048] (4) First, 4.46 mL of polyvinyl alcohol aqueous solution was slowly dripped into 9.00 mL of fluorinated graphene nanosheet dispersion under stirring, and the mixed solution was ultrasonicated for 10 min and stirred for 30 min; then, 0.58 mL of carboxymethyl chitosan aqueous dispersion was slowly dripped into it under stirring, and stirring was continued for 30 min; finally, the prepared mixed solution was poured into a quartz watch glass and dried in a conventional oven at a temperature of 60° C. to obtain a uniform light yellow transparent polyvinyl alcohol-based composite film, wherein the mass ratio of polyvinyl alcohol, fluorinated graphene nanosheets, and carboxymethyl chitosan was 100:3.4:8.7. The polyvinyl alcohol-based composite film prepared in this example is hereinafter referred to as PCF-3.
[0049] Example 3
[0050] (1) A suspension of fluorinated graphene and N-methylpyrrolidone was refluxed at 80°C for 2 h, ultrasonicated (40 W) for 24 h, and then centrifuged at 3000 and 6000 rpm for 30 min, respectively; the precipitate at 6000 rpm was washed with deionized water, filtered and freeze-dried to obtain fluorinated graphene nanosheets; and finally, the precipitate was redispersed in water under ultrasonication to obtain a 1.0 mg / mL aqueous dispersion of fluorinated graphene nanosheets.
[0051] (2) 4 g of polyvinyl alcohol particles were added to a beaker containing 100 mL of deionized water, stirred at 80° C. until completely dissolved, and deionized water was added to the 100 mL mark to obtain a 40 mg / mL polyvinyl alcohol aqueous solution.
[0052] (3) Add 3 g of carboxymethyl chitosan powder into a beaker containing 100 mL of deionized water and stir until dissolved to obtain a 30 mg / mL carboxymethyl chitosan aqueous solution.
[0053] (4) First, 3.28 mL of polyvinyl alcohol aqueous solution was slowly dripped into 7.50 mL of fluorinated graphene nanosheet dispersion under stirring, and the mixed solution was ultrasonicated for 10 min and stirred for 30 min; then, 0.38 mL of carboxymethyl chitosan aqueous dispersion was slowly dripped therein under stirring, and stirring was continued for 30 min; finally, the prepared mixed solution was poured into a quartz watch glass and dried in a conventional oven at a temperature of 60° C. to obtain a uniform light yellow transparent polyvinyl alcohol-based composite film, wherein the mass ratio of polyvinyl alcohol, fluorinated graphene nanosheets, and carboxymethyl chitosan was 100:5.7:8.7. The polyvinyl alcohol-based composite film prepared in this example is hereinafter referred to as PCF-5.
[0054] Example 4
[0055] (1) A suspension of fluorinated graphene and N-methylpyrrolidone was refluxed at 80°C for 2 h, ultrasonicated (40 W) for 24 h, and then centrifuged at 3000 and 6000 rpm for 30 min, respectively; the precipitate at 6000 rpm was washed with deionized water, filtered and freeze-dried to obtain fluorinated graphene nanosheets, and finally redispersed in water under ultrasonication to obtain a 1.0 mg / mL aqueous dispersion of fluorinated graphene nanosheets.
[0056] (2) Add 5 g of polyvinyl alcohol particles into a beaker containing 100 mL of deionized water, stir at 80° C. until completely dissolved, and add deionized water to the 100 mL mark to obtain a 50 mg / mL polyvinyl alcohol aqueous solution.
[0057] (3) Add 3 g of carboxymethyl chitosan powder into a beaker containing 100 mL of deionized water and stir until dissolved to obtain a 30 mg / mL carboxymethyl chitosan aqueous solution.
[0058] (4) First, 2.57 mL of polyvinyl alcohol aqueous solution was slowly dripped into 10.50 mL of fluorinated graphene nanosheet dispersion under stirring, and the mixed solution was ultrasonicated for 10 min and stirred for 30 min; then, 0.37 mL of carboxymethyl chitosan aqueous dispersion was slowly dripped into it under stirring, and stirring was continued for 30 min; finally, the prepared mixed solution was poured into a quartz watch glass and dried in a conventional oven at a temperature of 60° C. to obtain a uniform light yellow transparent polyvinyl alcohol-based composite film, wherein the mass ratio of polyvinyl alcohol, fluorinated graphene nanosheets, and carboxymethyl chitosan was 100:8.2:8.7. The polyvinyl alcohol-based composite film prepared in this example is hereinafter referred to as PCF-7.
[0059] In order to verify the technical effect of the present invention, polyvinyl alcohol (PVA) film, polyvinyl alcohol / fluorinated graphene nanosheet (PVA / FGN) composite film, polyvinyl alcohol / carboxymethyl chitosan (PVA / CMC) composite film were prepared respectively, and the performance was compared with the polyvinyl alcohol-based composite film of the present invention; the preparation methods of polyvinyl alcohol film, polyvinyl alcohol / fluorinated graphene nanosheet composite film, and polyvinyl alcohol / carboxymethyl chitosan composite film are shown in Comparative Examples 1 to 3 respectively:
[0060] Comparative Example 1
[0061] 3g of polyvinyl alcohol particles were added to a beaker containing 100mL of deionized water, stirred at 80°C until completely dissolved, and deionized water was added to the 100mL mark to obtain a 30mg / mL polyvinyl alcohol aqueous solution; the polyvinyl alcohol solution was placed in a quartz watch glass, dried and peeled off. The in-plane and out-of-plane thermal conductivity were tested to be 0.28W / (m·K) and 0.10W / (m·K), respectively.
[0062] Comparative Example 2
[0063] (1) A suspension of fluorinated graphene and N-methylpyrrolidone was refluxed at 80°C for 2 h, ultrasonicated (40 W) for 24 h, and then centrifuged at 3000 rpm and 6000 rpm for 30 min, respectively; the precipitate at 6000 rpm was washed with deionized water, filtered and freeze-dried to obtain fluorinated graphene nanosheets; and then redispersed in water under ultrasonication to obtain a 0.5 mg / mL aqueous dispersion of fluorinated graphene nanosheets.
[0064] (2) Add 5 g of polyvinyl alcohol particles into a beaker containing 100 mL of deionized water, stir at 80° C. until completely dissolved, and add deionized water to the 100 mL mark to obtain a 50 mg / mL polyvinyl alcohol aqueous solution.
[0065] (3) First, 2.91 mL of polyvinyl alcohol solution was slowly dripped into 9.00 mL of fluorinated graphene nanosheet dispersion under stirring. The mixed solution was ultrasonicated for 10 min and stirred for 30 min. The prepared mixed solution was poured into a quartz watch glass and dried in a conventional oven at 60° C. to obtain a composite film containing 3 wt.% of fluorinated graphene nanosheets.
[0066] The in-plane and out-of-plane thermal conductivities of the composite film (containing 3 wt. % of fluorinated graphene nanosheets) are 2.34 W / (m·K) and 0.08 W / (m·K), respectively.
[0067] Comparative Example 3
[0068] (1) Add 5 g of polyvinyl alcohol particles into a beaker containing 100 mL of deionized water, stir at 80°C until completely dissolved, and add deionized water to the 100 mL mark to obtain a 50 mg / mL polyvinyl alcohol aqueous solution.
[0069] (2) Add 3 g of carboxymethyl chitosan powder into a beaker containing 100 mL of deionized water and stir until dissolved to obtain a 30 mg / mL carboxymethyl chitosan aqueous solution.
[0070] (3) First, 2.76 mL of polyvinyl alcohol solution was slowly dripped into 0.40 mL of carboxymethyl chitosan aqueous dispersion under stirring, and stirring was continued for 30 min; the prepared mixed solution was poured into a quartz watch glass, and dried in a conventional oven at a temperature of 60° C. to obtain a composite film containing 8 wt.% of carboxymethyl chitosan.
[0071] The in-plane and out-of-plane thermal conductivities of the composite film (containing 8 wt. % of carboxymethyl cellulose) are 0.81 W / (m·K) and 0.21 W / (m·K), respectively.
[0072] Figure 1 The scanning electron microscope images of the films of Examples 2 and 3 of Comparative Example 1 are shown; wherein (a), (b), and (c) correspond to the surfaces of the three films in turn, and (d), (e), and (f) correspond to the brittle fracture surfaces of the three films in turn. Through the scanning electron microscope, it can be observed that the fluorinated graphene nanosheets in the Example 2 film prepared in Example 2 are evenly distributed in polyvinyl alcohol, without filler accumulation, and the inter-sheet spacing is about 0.5 μm, while most of the fluorinated graphene in the PCF-5 film of Example 3 can be evenly dispersed, but there is a small amount of filler accumulation, and the inter-sheet spacing is significantly reduced compared to the Example 2 film, indicating that the amount of fluorinated graphene in the Example 2 film has reached its dispersion threshold in polyvinyl alcohol.
[0073] Figure 2The DSC graphs of the films of Examples 1 to 4 and Comparative Examples 1 to 3 are shown, and Table 1 lists the data related to the DSC graphs and the crystallinity of the composite films. The above data show that the crystallinity of the composite films increases first and then decreases with the increase in the amount of fluorinated graphene added, and the crystallinity of the films of Comparative Example 2 and Example 2 is the highest. It can be inferred that polyvinyl alcohol will be oriented and crystallized at the edge of the fluorinated graphene, and the permeation threshold of the fluorinated graphene in polyvinyl alcohol is 3wt.%. The difference between the two is that the melting point and glass transition temperature of the film of Example 2 are significantly higher than those of the film of Comparative Example 2, indicating that the film of Example 2 has a complete thermal conductivity network, which can transfer heat well when heated.
[0074] Table 1
[0075]
[0076] Figure 3 (a) shows the stress-strain curves of the films of Examples 1 to 4 and Comparative Examples 1 to 3, wherein the tensile strength of Example 2 is 61.2 MP, which is lower than the films of Comparative Examples 1 and 3, but significantly higher than the film of Comparative Example 2, indicating that although the crystallinity of the composite film increases after the addition of fluorinated graphene nanosheets, the random arrangement of the fluorinated graphene nanosheets increases the disorder of the crystal regions, and the tensile strength decreases instead. The addition of carboxymethyl chitosan can effectively connect adjacent crystal regions, thereby improving the tensile strength. Figure 3 (b) shows the volume resistivity diagram of the films of Examples 1 to 4 and Comparative Examples 1 to 3. The volume resistivity of all the films is greater than>10 11 Ω·m, indicating that all prepared films have good insulation properties.
[0077] Figure 4 The bar graphs of the in-plane and out-of-plane thermal conductivity coefficients of the films of Examples 1 to 4 and Comparative Examples 1 to 3 show that when 3 wt.% of fluorinated graphene and 8 wt.% of carboxymethyl chitosan are added to polyvinyl alcohol, respectively, the in-plane and out-of-plane thermal conductivities of the films of Comparative Examples 2 and 3 are only slightly improved compared to those of the film of Comparative Example 1, while the thermal conductivity of the film of Example 2 is significantly improved, with in-plane and surface thermal conductivities of 12.22 W / (m·K) and 0.81 W / (m·K), respectively, which are 43.6 and 8.1 times that of the film of Comparative Example 1, indicating that a good thermal conductive network is formed inside the film after the addition of carboxymethyl chitosan.
[0078] Figure 5 (a) shows the infrared thermal imaging of LED bulbs with the films of Comparative Examples 1 to 3 and Example 2 as substrates. The film of Example 2 can reduce the temperature of the bulb to 52°C at 180s, which is significantly better than the films of Comparative Examples 1 to 3. Moreover, the temperature has basically stabilized after 120s, indicating that the composite film has good comprehensive thermal conductivity. Figure 5(b) shows the infrared thermal imaging images of the films of Comparative Examples 1 to 3 and Example 2 in the perpendicular plane direction. It can be seen that the temperature of the film of Comparative Example 2 is the lowest at 15s, indicating that its out-of-plane thermal conductivity is the lowest. Although it has a large degree of crystallinity, the disordered arrangement of the crystal regions is not conducive to heat transfer. The temperature of Comparative Example 2 is the highest, indicating that the carboxymethyl chitosan connects adjacent crystal regions and forms a good thermal conductive network, and its out-of-plane thermal conductivity is significantly improved.
[0079] In the present invention, after adding fluorinated graphene to polyvinyl alcohol, it is found through DSC calculation that the crystallinity of the prepared composite film is significantly increased, and since there are a large number of F bonds at the edge of fluorinated graphene that can form hydrogen bonds with polyvinyl alcohol, it is speculated that the increase in crystallinity is the result of polyvinyl alcohol being oriented and crystallized at the edge of fluorinated graphene. However, at this time, the random arrangement of fluorinated graphene leads to an increase in the disorder of the crystalline region, and its thermal conductivity increases to a limited extent, and its out-of-plane thermal conductivity is even lower than that of polyvinyl alcohol. After adding carboxymethyl chitosan, its tensile strength and thermal conductivity are greatly improved compared to the polyvinyl alcohol-based composite film with only fluorinated graphene added, indicating that carboxymethyl chitosan can connect adjacent crystalline regions through hydrogen bond coupling, thereby forming an efficient heat-conducting network composed of carboxymethyl chitosan-crystalline region-fluorinated graphene.
[0080] Since the polyvinyl alcohol-based composite film of the present invention has excellent electrical insulation properties, mechanical properties and thermal properties, it can be widely used in applications with high requirements for thermal conductivity and insulation, and is suitable for closed or continuous working scenarios. For example, it can be applied as a protective film on the surface of power electronic components, thereby ensuring electrical insulation while greatly improving the upper limit of the operating temperature of the components through good heat dissipation.
Claims
1. A polyvinyl alcohol-based composite film, characterized in that: It is composed of polyvinyl alcohol, fluorinated graphene nanosheets and carboxymethyl chitosan in a mass ratio of 100:1.1~8.2:8.
7. Polyvinyl alcohol connects to fluorinated graphene nanosheets through hydrogen bonds, and directionally arranges and crystallizes at their edges. Carboxymethyl chitosan couples adjacent polyvinyl alcohol crystal regions through hydrogen bonds, thus forming an efficient thermal conductive network composed of carboxymethyl chitosan-crystal region-fluorinated graphene.
2. The polyvinyl alcohol-based composite film according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol, fluorinated graphene nanosheets and carboxymethyl chitosan is 100:1.1 to 3.4:8.
7.
3. The polyvinyl alcohol-based composite film according to claim 2, characterized in that: Fluorinated graphene nanosheets account for 3% of the mass.
4. The method for preparing a polyvinyl alcohol-based composite film according to any one of claims 1 to 3, characterized in that: A polyvinyl alcohol aqueous solution with a concentration of 20-50 mg / mL and a fluorinated graphene nanosheet aqueous dispersion with a concentration of 0.5-1 mg / mL are mixed evenly according to the mass ratio, and then 20-30 mg / mL of a carboxymethyl chitosan aqueous dispersion is added and mixed evenly. After vacuum drying at a temperature of 60° C. to 80° C. into a film, it is peeled off from the carrier.
5. The preparation method according to claim 4, characterized in that: The preparation method of the fluorinated graphene nanosheet is as follows: dispersing the fluorinated graphene in a solvent, and subjecting the solvent to ultrasonic and centrifugal treatment to obtain an exfoliated fluorinated graphene nanosheet.
6. The preparation method according to claim 5, characterized in that: The ultrasonic treatment is performed using a water bath sonicator, the power of the water bath sonicator is 30-100 W, and the ultrasonic time is 18-32 h; the rotation speed of the centrifugal treatment is 3000-6000 rpm, and the treatment time is 15-30 min.
7. The preparation method according to claim 5, characterized in that: The solvent is one or more of isopropanol, N-methylpyrrolidone, N,N-dimethylformamide and dichloromethane.
8. The preparation method according to claim 4, characterized in that: The fluorinated graphene nanosheet aqueous dispersion, the polyvinyl alcohol aqueous solution and the carboxymethyl chitosan aqueous dispersion are uniformly mixed by ultrasonic and stirring.
9. Use of the polyvinyl alcohol-based composite film as claimed in any one of claims 1 to 3 as a protective film on the surface of power electronic components.
Citation Information
Patent Citations
Flexible and electrically insulating fluorinated graphene heat-conducting composite film as well as preparation and application thereof
CN109912912A
Polymer composite material as well as preparation method and application thereof
CN114456526A
Electroconductive hydrogel and devices with conducting polymers assembled around a 3D nanofiber framework
US20240263002A1